2021
DOI: 10.1016/j.sleepx.2021.100036
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the link between sleep and postpartum depression in fathers utilizing subjective and objective sleep measures

Abstract: Background While fathers are at risk of developing poorer sleep and depressive symptoms in the postpartum period, they represent an understudied population in the literature. The present study aimed to explore the association between sleep and postpartum depressive symptoms in fathers using subjective and objective sleep measures. Methods Fifty-four fathers reporting no history of depression took part in this cross-sectional study. At 6 months postpartum, paternal sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…A link between sleep disturbances and paternal postnatal depression has been well documented (Da Costa et al, 2015; Kalogeropoulos et al, 2021). This study also found sleep disturbance to be a risk factor of paternal postnatal depression in Pakistani men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A link between sleep disturbances and paternal postnatal depression has been well documented (Da Costa et al, 2015; Kalogeropoulos et al, 2021). This study also found sleep disturbance to be a risk factor of paternal postnatal depression in Pakistani men.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found sleep disturbance to be a risk factor of paternal postnatal depression in Pakistani men. Kalogeropoulos et al investigated the association between sleep and postnatal depressive symptoms in 54 Canadian fathers (previously not diagnosed with depression) using subjective and objective sleep measures and found that self‐reported perceived sleep quality was significantly associated with paternal postnatal depression, with first‐time fathers more likely to suffer from depression due to sleep disturbances in the postnatal period (Kalogeropoulos et al, 2021). Despite not having a direct role in caring responsibilities of the newborn, 33% of the fathers in our study reported sleep disturbances during the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, participants with poor satisfaction had a 3.1-fold increased likelihood of experiencing greater than minimal depressive symptoms, whereas those with lower alertness had a 1.9-fold increased likelihood of experiencing greater than minimal depressive symptoms. Previous studies reported that poor subjective sleep satisfaction was associated with postpartum depression in mothers, but objectively measured sleep data, including sleep duration, efficiency, and disturbances, were not associated with depressive symptoms (55,56). Taken together, these findings suggest that individuals’ perception of sleep may be more salient for depressive symptoms than objective measures of sleep.…”
Section: Discussionmentioning
confidence: 98%
“…The Kessler Psychological Distress Scale (K10) (Kessler et al, 2002) Infant issues are one of the antecedents of perinatal depression in fathers. Parenting can be challenging for first-time fathers, which lack parenting skills and experience (Kalogeropoulos et al, 2021). A child crying and disrupting the rhythm of life could cause sleep problems for the father and lead to depressed moods.…”
Section: Scalementioning
confidence: 99%